ANALISIS NORMATIF TERHADAP JAMINAN HAK ATAS TANAH DAN BANGUNAN DEBITUR YANG BERSERTIPIKAT TUMPANG TINDIH SAAT AKAN DI EKSEKUSI - ISABELLA BANGUN (PREMISE LAW JURNAL, 2016)
In its development nowadays, land becomes the most common problem, particularly about the overlapping certificates. In general, the problem about this overlapping certificate occurred in a tract of land which has double certificates and the owner of the land want to or has done legal action on the land. For example, a land certificate is used as collateral in a Bank, but execution cannot be accomplished because there is another person who has the certificate on the land. Therefore, the researcher wanted to find out what factors which caused the incident of overlapping certificates and how about the legal protection for the Bank as the creditor. The result of the research shows that the factor which causes the incident of overlapping certificate is administrative error (internal factor) done by some employees intentionally for their own interest in the Land Office, while the external factor of the Land Office is the bad intention of the person who requests his right for registering the certificate, Therefore, the management of the Land Office as the institution which issues land rights certificates is not responsible for the existence of overlapping certificate although they are always ready to be the mediator in resolving the dispute about overlapping certificate by doing the study on physical and judicial data. The Bank, as the creditor for this problematic collateral, does not get any legal protection because there is no regulation in the legal provisions although the creditor can file the claim to the debtor, since the latter has violated the law, by asking for compensation from the debtor when the judge gives the verdict that the land belongs to the third party. Keywords : Overlapping Certificate, Collateral